Creating a Classroom of Connoisseurs: Grade 7 Students and Their Teacher Investigate Their Growth As Readers - Maria Kowal (Networks: An Online Journal for Teacher Research, 2003)
Maria Pia's poem illustrates the state of mind I was in. It was August and I was preparing for the upcoming school year. My assignment, as it had been for a few years, was Grade 7 home room teacher, responsible for teaching language arts, social studies and math to 12 and 13 year olds. My thoughts were tuned in to my language arts program; the reading component in particular. The purpose of this paper is to show how over the course of a school year, through coinvestigating this aspect of my program with my students, I and they came to gain a deeper understanding of how young adolescent readers can make meaning from the texts they read.